Cellular Immune Response to COVID-19 and Potential Immune Modulators - Zhou, Xi; Ye, Qing (Frontiers in Immunology, 2021)
Coronavirus disease 2019 (COVID-19) is a respiratory infectious disease caused by SARS-CoV-2, and droplets and contact serve as the main route of transmission. Although most patients have mild symptoms and good prognosis after infection, some patients develop severe respiratory infection, multiple organ failure or even death. Interindividual clinical variability is large in each demographic category, and the factors associated with the outcome of COVID-19 have not been completely characterized to date. Inspired by previous studies on the relevance of infectious diseases, viral and host factors related to clinical outcomes have been identified. The viral SARS-COV-2 genome is largely stable, and no significant correlation was noted between COVID-19 severity and genetic variation of the virus or the patient's initial viral load. Hence, the severity of COVID-19 is mostly related to host factors, especially cellular immune responses in patients. Patients with mild COVID-19 and improved patients with severe COVID-19 exhibit a normal immune response that can effectively eliminate the virus. The immune response in patients with fatal severe COVID-19 includes three stages: normal or hypofunction, hyperactivation, and anergy. Eventually, the patients were unable to resist viral infection and died. Based on our understanding of the kinetics of immune responses during COVID-19, we suggest that type I IFN could be administered to patients with severe COVID-19 in the hypofunctional stage, and IVIG and glucocorticoid therapy could be administered in the immune hyperactivation stage. In addition, LMWH anticoagulation therapy and anti-infective therapy with antibiotics are recommended in the hyperactivation stage.